Empowering Civic Engagement Through Digital Citizenship Education: A Cross-Cultural Perspective - Rizal, Andi; ., Burhan; Irwandi, Andi; ., Nurwidyayanti; Muhammad, Achmad Fajar (Journal of Ecohumanism, 2025)
Digital citizenship education is a vital component of fostering responsible and active civic engagement in the digital age. This study examines the role of cultural contexts in shaping digital citizenship education and its potential to empower individuals across different societies. Through a cross-cultural perspective, the research explores how digital citizenship programs are designed and implemented in collectivist, individualist, and transitional societies, with a focus on how these programs address the needs of diverse learners. The findings highlight that cultural norms significantly influence the emphasis placed on community values, individual autonomy, and local issues in digital citizenship curricula. Collectivist societies prioritize collective responsibility and social cohesion, while individualist societies emphasize personal expression and critical thinking. In transitional societies, digital citizenship education serves to bridge digital divides and address socio-economic challenges. The study also underscores the transformative potential of digital citizenship education in fostering civic awareness, critical digital literacy, and social advocacy. However, the research identifies challenges, such as access disparities, resistance to change, and ethical concerns, which must be addressed to maximize the impact of digital citizenship programs. The study concludes that tailoring digital citizenship education to local cultural contexts and addressing the specific challenges of each society can empower individuals to navigate and contribute to the digital world responsibly. This research provides valuable insights for policymakers, educators, and stakeholders looking to enhance the design and implementation of digital citizenship education globally.